Polysaccharide utilisation loci of Bacteroidetes from two contrasting open ocean sites in the North Atlantic. (18th July 2016) - Bennke, Christin M.; Krüger, Karen; Kappelmann, Lennart; Huang, Sixing; Gobet, Angélique; Schüler, Margarete; Barbe, Valérie; Fuchs, Bernhard M.; Michel, Gurvan; Teeling, Hanno; Amann, Rudolf I.
Summary: Marine Bacteroidetes have pronounced capabilities of degrading high molecular weight organic matter such as proteins and polysaccharides. Previously we reported on 76 Bacteroidetes ‐affiliated fosmids from the North Atlantic Ocean's boreal polar and oligotrophic subtropical provinces. Here, we report on the analysis of further 174 fosmids from the same libraries. The combined, re‐assembled dataset (226 contigs; 8.8 Mbp) suggests that planktonic Bacteroidetes at the oligotrophic southern station use more peptides and bacterial and animal polysaccharides, whereas Bacteroidetes at the polar station (East‐Greenland Current) use more algal and plant polysaccharides. The latter agrees with higher abundances of algae and terrigenous organic matter, including plant material, at the polar station. Results were corroborated by in‐depth bioinformatic analysis of 14 polysaccharide utilisation loci from both stations, suggesting laminarin‐specificity for four and specificity for sulfated xylans for two loci. In addition, one locus from the polar station supported use of non‐sulfated xylans and mannans, possibly of plant origin. While peptides likely represent a prime source of carbon for Bacteroidetes in open oceans, our data suggest that as yet unstudied clades of these Bacteroidetes have a surprisingly broad capacity for polysaccharide degradation. In particular, laminarin‐specific PULs seem widespread and thus must be regarded as globally important.